Immunosenescence: what does it mean to health outcomes in older adults? - McElhaney, Janet E; Effros, Rita B (Current opinion in immunology, 2009)
The most profound consequences of immune senescence with respect to human health are the increased susceptibility to infectious diseases and decreased vaccine efficacy. Changes in both innate and adaptive immune function converge in the reduced response to vaccination and protection against infection and related diseases. The decline in thymic output of naïve T cells diminishes responses to novel antigens, such as West Nile Virus, while clonal expansions leading to defects in the T cell repertoire are associated with blunted responses of memory T cells to conserved epitopes of the influenza virus. Recent studies on how immunologic mechanisms of protection change during aging have led to novel strategies for improving vaccine responsiveness and outcomes of infectious diseases in older adults.